2021
DOI: 10.1136/bmjopen-2020-039070
|View full text |Cite
|
Sign up to set email alerts
|

Active & Safe Central: using a mixed-methods design and the RE-AIM framework to evaluate a sport and recreational injury prevention resource for practitioners in Canada

Abstract: ObjectivesAn online, evidence-based resource was created to support the development of sport and recreational injury prevention programmes. The resource, called Active & Safe Central (www.activesafe.ca), provides evidence-based information across the public health approach for a number of sport and recreational activities. The objective of this project was to evaluate the perceived usefulness of Active & Safe Central as an educational tool.DesignA mixed-methods study design, guided by the RE-AIM (reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…There are, however, a number of studies which have examined reach for efforts designed to engage with and inform knowledge users in related contexts—including injury prevention and neurotrauma. For example, Richmond et al 29 demonstrated that 5% of users who accessed a newly-developed web-based resource designed to raise knowledge and awareness of ways to reduce injury risk in sport and recreational activity went on to complete a survey asking them about their experience. Furthermore, Sweet et al 30 showed that 28% of the intended audience was reached for a knowledge mobilization activity with the objective of developing solutions to translating research into practice in the spinal cord injury community.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, a number of studies which have examined reach for efforts designed to engage with and inform knowledge users in related contexts—including injury prevention and neurotrauma. For example, Richmond et al 29 demonstrated that 5% of users who accessed a newly-developed web-based resource designed to raise knowledge and awareness of ways to reduce injury risk in sport and recreational activity went on to complete a survey asking them about their experience. Furthermore, Sweet et al 30 showed that 28% of the intended audience was reached for a knowledge mobilization activity with the objective of developing solutions to translating research into practice in the spinal cord injury community.…”
Section: Discussionmentioning
confidence: 99%
“…Existing injury-related implementation studies and commentaries can help guide researchers in their efforts in this regard, as well as in alternative ways of disseminating research findings (e.g., Acland, 2016;Benjaminse & Verhagen, 2021;Donaldson et al, 2017;Richmond et al, 2021).…”
Section: Conducting Pragmatic and Implementationmentioning
confidence: 99%
“…These include, among others, the institution of the B.C. Injury Research and Prevention Unit (BCIRPU), the development of the Canadian Falls Prevention Curriculum [9], Preventable [10][11][12], Road Safety Strategy 2015 and Beyond [13], Concussion Awareness Training Tool (CATT) [14,15], and Active & Safe Central [16]. One of the essential components required for successful and sustainable implementation of public health interventions includes the communication of accurate, timely, and concise information to decision-makers and other key stakeholders [17].…”
Section: Introductionmentioning
confidence: 99%